BLOOD PRESSURE RESPONSE TO AN ISOMETRIC CONTRACTION AND 3 MINUTE OF TREADMILL TEST PREDICTS LEFT VENTRICULAR HYPERTROPHY IN NORMOTENSIVES. (April 2021) - Pittaras, Andreas; Faselis, Charles; Grassos, Haralampos; Poulimenos, Leonidas; Doumas, Michel; Stavropoulos, Konstantinos; Kyfnidis, Konstantinos; Samuel, Immanuel; Pyriovoli, Georgia; Kallistratos, Manolis; Imprialos, Konstantinos; Manolis, Athanasios; et al.
Abstract : Objective: Left ventricular hypertrophy (LVH) is associated with a significant increase in major CV event. Recent evidence supports the presence of LVH independent of BP and other confounders. The presence of LVH, especially in those with normal resting BP, is likely to remain undetected in this cohort for two main reasons: 1) The misconception that LVH only occurs when hypertension is present and, 2) The non-invasive methods to screen for LVH either have poor sensitivity (EKG) or are relatively costly and labor intensive (Echo, MRI). We hypothesized that BP response in isometric contraction, and exercise treadmill test, will be significantly associated with cardiac structure and function, providing an inexpensive and practical screening method to identify pts at high risk of LVH. Design and method: In 344 men and 46 women, normotensives with no ECG-LVH, we assessed BP response: 1) during an isometric contraction (HGR) using 50% of the maximum force generated (1-RM) and 2) at 3 min of exercise treadmill test (ETT). Cardiac structure was assessed via echocardiogram. We used a logistic regression to determine the relationship between HGR-BP, ETT-BP and LVH, with LVH as the dependent variable. The model was adjusted for age and resting BP.. Results: Both HGR-SBP/DBP, and ETT-3min-SBP/DBP were significant predictors of LVH (p < 0.05). Inflection point analysis identified a HGR-SBP/DBP threshold of 146/84mmHg and ETT-SBP/DBP threshold 141/78 mmHg. Beyond these thresholds, the probability of LVH increased by 3% for every 1 mmHg change in SBP and 6% in DBP for HGR, and 2% & 4% for ETT-SBP/DBP respectively. The sensitivity and specificity of HG-SBP test was 90% and 79% The sensitivity and specificity of ETT-SBP-3 min test was 90% and 82% Conclusions: Both HGR-SBP/DBP and ETT-3min-SBP/DBP were strong predictors of LVH in normotensive subjects with no evidence of ECG-LVH, having clinically significant sensitivity and specificity.